2005
DOI: 10.1051/forest:2005037
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of irradiance and water availability on the photosynthetic performance of Picea sitchensis seedlings: implications for seedling establishment under different management practices

Abstract: -The impact of water availability on the photosynthetic performance of three year old, commercially obtained, Sitka spruce (Picea sitchensis) seedlings under exposed and shaded conditions was evaluated to provide a physiological understanding of the factors controlling seedling performance under conventional and continuous cover forestry (CCF) management scenarios. Decreases in photosynthesis in response to water deficits, under exposed and shaded conditions, were associated with reductions in both stomatal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Flexas et al (2012) set an average g m slightly above 100 mmol m –2 s –1 for conifers, and studies have shown a wide variation from as low as 18 up to 110 mmol m –2 s –1 in evergreen gymnosperms (Warren et al , 2003; De Lucia et al , 2003; Manter and Kerrigan, 2004; Black et al , 2005; Mullin et al , 2009; Peguero-Pina et al , 2012, 2016). Accordingly, g m varied from 10 to 124 mmol m –2 s –1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Flexas et al (2012) set an average g m slightly above 100 mmol m –2 s –1 for conifers, and studies have shown a wide variation from as low as 18 up to 110 mmol m –2 s –1 in evergreen gymnosperms (Warren et al , 2003; De Lucia et al , 2003; Manter and Kerrigan, 2004; Black et al , 2005; Mullin et al , 2009; Peguero-Pina et al , 2012, 2016). Accordingly, g m varied from 10 to 124 mmol m –2 s –1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with modelling predictions [53] which indicated that a minimum of 20% transmittance would be necessary for seedling survival under a canopy. The various trials also suggest that optimal conditions for early survival and growth of Sitka spruce seedlings are likely to be found in conditions of about 50-60% RLI, since under full light seedlings may suffer from frost damage [46] or from moisture stress due to higher evaporative demand [47]. The few comparisons of growth and survival of Sitka spruce and other species under a range of light conditions [46,49] tended to confirm the categorisation of Sitka spruce as having only intermediate shade tolerance.…”
Section: Minimum Light Environmentmentioning
confidence: 97%
“…Several studies have examined the survival and growth of Sitka spruce seedlings in relation to light climate [46][47][48][49][50][51][52]. These used a mixture of greenhouse and nursery studies or field trials of varying duration (Table 1) to try to determine the most favourable understorey environment for regenerating or under-planted seedlings.…”
Section: Minimum Light Environmentmentioning
confidence: 99%
“…Concerning g m in particular, values had been reported for a single moss species (Hanson et al ., ), six liverwort species (Meyer et al ., ), a single pteridophyte species (Volkova et al ., ) and no single lycophyte species. Even for gymnosperms, the number of species for which g m had been determined was lower than 15 species (DeLucia et al ., ; Manter and Kerrigan, ; Black et al ., ; Peguero‐Pina et al ., ). Moreover, the mechanisms behind the observed g m had not been studied in any of these species, with the exception of two gymnosperms of the genus Abies , for which anatomical constraints to g m were reported (Peguero‐Pina et al ., ).…”
Section: Introductionmentioning
confidence: 99%